Beyond debuttressing: Mechanics of paraglacial rock slope damage during repeat glacial cycles. Issue 4 (28th April 2017) - Grämiger, Lorenz M.; Moore, Jeffrey R.; Gischig, Valentin S.; Ivy‐Ochs, Susan; Loew, Simon
Abstract: Cycles of glaciation impose mechanical stresses on underlying bedrock as glaciers advance, erode, and retreat. Fracture initiation and propagation constitute rock mass damage and act as preparatory factors for slope failures; however, the mechanics of paraglacial rock slope damage remain poorly characterized. Using conceptual numerical models closely based on the Aletsch Glacier region of Switzerland, we explore how in situ stress changes associated with fluctuating ice thickness can drive progressive rock mass failure preparing future slope instabilities. Our simulations reveal that glacial cycles as purely mechanical loading and unloading phenomena produce relatively limited new damage. However, ice fluctuations can increase the criticality of fractures in adjacent slopes, which may in turn increase the efficacy of fatigue processes. Bedrock erosion during glaciation promotes significant new damage during first deglaciation. An already weakened rock slope is more susceptible to damage from glacier loading and unloading and may fail completely. We find that damage kinematics are controlled by discontinuity geometry and the relative position of the glacier; ice advance and retreat both generate damage. We correlate model results with mapped landslides around the Great Aletsch Glacier. Our result that most damage occurs during first deglaciation agrees with the relative age of the majority of identified landslides. The kinematics and dimensions of a slope failure produced in our models are also in good agreement with characteristics of instabilities observed in the field. Our results extend simplified assumptions of glacial debuttressing, demonstrating in detail how cycles of ice loading, erosion, and unloading drive paraglacial rock slope damage. Key Points: Simply adding then removing glacier ice from an alpine valley has little net effect on rock wall damage Glacial erosion, i.e., rock debuttressing, creates significant new rock slope damage during first deglaciation Damage kinematics vary during a glacial cycle: ice advance favors toppling, while retreat promotes sliding